Brands and branding: Strategy to build and nurture brands - Aggarwal, Ashita; Commuri, Suraj (London Routledge, 2024)
This volume examines the importance of strategic brand imaging and brand management. It covers the fundamentals of launching, growing, leveraging, and managing brands in a global context, the strategic decisions related to brand building, and the integration of the 4Ps in implementing the brand strategy. The book presents a practical perspective on building brands through social media and using artificial intelligence technologies. Readers will get a clear introductory understanding about the role of consumer behavior, the research methods that every brand manager must be familiar with, brand architecture, portfolio, brand equity, and valuation. Branding requires vision to foresee, logic to understand the market, and the art of understanding consumers. This book is a guide for readers and professionals who are interested in all
Keywords: Brands- social media; Consumer Behavior; Brand management